Evaluation of a Dedicated Software “Elements™ Spine SRS, Brainlab®” for Target Volume Definition in the Treatment of Spinal Bone Metastases With Stereotactic Body Radiotherapy - Rogé, Maximilien; Henni, Ahmed Hadj; Neggaz, Yasmine Adda; Mallet, Romain; Hanzen, Chantal; Dubray, Bernard; Colard, Elyse; Gensanne, David; Thureau, Sébastien (Frontiers in Oncology, 2022)
Introduction:Stereotactic body radiotherapy (SBRT) is a treatment option for spine metastases. The International Spine Radiosurgery Consortium (ISRC) has published consensus guidelines for target delineation in spine SBRT. A new software called Elements™ Spine SRS by Brainlab® that includes the module Elements SmartBrush Spine (v3.0,Munich,Germany) has been developed specifically for SBRT treatment of spine metastases and the latter provides the ability to perform a semi-automatic clinical target volume (CTV) generation based on the gross tumor volume (GTV) localization and guidelines. The aims of our study were to evaluate this software by studying differences in volumes between semi-automatic CTV contours compared to a manual contouring performed by an expert radiation oncologist and to determine the dosimetric impact of these differences on treatment plans. Methods:35 volumes ("Expert GTV" and “Expert CTV”) from 30 patients were defined by a single expert. A semi-automatic definition of these 35 CTVs based on the location of “Expert GTV” and following ISRC Guidelines was also performed in Elements SmartBrush Spine (“Brainlab CTV”). The spatial overlap between “Brainlab” and “Expert” CTVs was calculated using the Dice similarity coefficient (DSC). We considered a threshold of 0.80 or above to indicate that Elements SmartBrush Spine performed very well with adequate contours for clinical use. Two dosimetric treatment plans, each corresponding to a specific planning target volume (PTV; Expert PTV,Brainlab PTV), were created for 11 patients. Results:We showed that “Brainlab CTV” and “Expert CTV” mean volumes were 29.8+/-16.1 and 28.7+/-15.7 cm3, respectively (p=0.23). We also showed that the mean DSC for the semi-automatic contouring relative to the expert manual contouring was 0.85 +/- 0.08 and less than 0.80 in 5 cases. For metastases involving the vertebral body only (n=13,37%), mean DSC was 0.90+/-0.03 and for ones involving other or several vertebral regions (n=22,63%), mean DSC was 0.81+/-0.08 (p<0.001). The comparison of dosimetric treatment plans was performed for equivalent PTV coverage. There was no differences between doses received by OARs (spinal cord and esophagus) for Expert and Brainlab PTVs, respectively. Conclusion:The results showed that the semi-automatic method had a quite good accuracy and can be used in clinical routine even for complex lesions.